Um estudo descritivo dos predicadores experienciais psicológicos, físicos, epistêmicos e de percepção do português: análise das correlações sintático-semânticas orientada pela freqüência dos tipos de construções morfológicas - Gabriele Cristine Carvalho (2008)
The present research addresses the study of experiential predicators. Experiential predicators bear an experience argument and express events of cognition, emotion and sensation (physical or psychological). The following variables were selected for this analysis: the variation ofpronoun constructions, the properties related to the experienciers distribution in accordance with its syntactic function, the mophological structure of the predicators and the lexical item.Guided by the Theory of Variation and according to Labov (1972, 2001), this research was based on usage data obtained from taped interviews with residents of Santa Luzia city. All experiential predicators occurrences were registered, allowing the organization of a corpus constituted by 1932 data. The research analysis was guided by the assumptions that thecontext of the pronoun is reduced because of the great amount of periphrastic constructions made by experiential predicators, and that such a characteristic may be variable according to the semantic features of the predicators. Verification of these hypotheses determined theconsideration of different corpora, in which global occurrences were divided across the analysis. The outcomes of the quantitative analysis (where the analysis program of multiple variables of Goldvarb/Varbrul 2001 was used) showed that the context of pronoun is ratherreduced, the indexes of pronoun use are practically null, and the relations between syntactic and morphological features of predicators are usually subject to the their semantic features. Idiosyncratic behaviors were identified in all stages of the analysis, which allowed the indication of an interference of the lexical item factor.